Traditionally available street food the market free from harmful chemical additives - Shalihat Afifah Dhaningtyas; Aditia Fajar Putra Wibowo; Hanif Khoiry Syammakh; Muhammad Surya Anggara; Qurrota A’yun; Olivia Rahmadhani (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
All living organisms, including humans, require food to sustain life. Unsafe food leads to health problems. Therefore, this study evaluates the chemical parameters of commonly consumed food items. The research was conducted in a laboratory using a descriptive observational approach to analyze chemical components in selected food samples. A purposive sampling method was employed for sample selection. Testing for borax using the ethanol method, while testing for formalin, rhodamine B, and methyl yellow using a test kit. The results revealed that all tested food samples were free from harmful chemical additives. Specifically, salted fish and wet noodles tested negative for formalin; meatballs and cilok were free of borax; chicken noodle sauce and red sausage did not contain rhodamine B; yellow crackers and yellow tofu tested negative for methyl yellow.  The conclusion of this study was that all food samples tested were safe for consumption